Bioelectrochemical sensing of promethazine with bamboo-type multiwalled carbon nanotubes dispersed in calf-thymus double stranded DNA - Primo, Emiliano Nicolás (2014)
We report the quantification of promethazine (PMZ) using glassy carbon electrodes (GCE) modified with bamboo-like multi-walled carbon nanotubes (bCNT) dispersed in double stranded calf-thymus DNA (dsDNA) (GCE/bCNT-dsDNA). Cyclic voltammetry measurements demonstrated that PMZ presents a thin film-confined redox behavior at GCE/bCNT-dsDNA, opposite to the irreversibly-adsorbed behavior obtained at GCE modified with bCNT dispersed in ethanol (GCE/bCNT). Differential pulse voltammetry-adsorptive stripping with medium exchange experiments performed with GCE/bCNT-dsDNA and GCE modified with bCNTs dispersed in single-stranded calf-thymus DNA (ssDNA) confirmed that the interaction between PMZ and bCNT-dsDNA is mainly hydrophobic. These differences are due to the intercalation of PMZ within the dsDNA that supports the bCNTs, as evidenced from the bathochromic displacement of UV–Vis absorption spectra of PMZ and quantum dynamics calculations at DFTB level. The efficient accumulation of PMZ at GCE/bCNT-dsDNA made possible its sensitive quantification at nanomolar levels (sensitivity: (3.50 ± 0.05) × 108 μA·cm− 2·M− 1 and detection limit: 23 nM). The biosensor was successfully used for the determination of PMZ in a pharmaceutical product with excellent correlation.